Implementasi Perencanaan Berbasis Partisipatif Dalam Pembangunan Jembatan Gantung di Desa Air Merah Kabupaten Labuhan Batu Selatan - Dinda Adelia (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2022)
The purpose of this study is to determine the implementation of participatory-based planning in the construction of a suspension bridge in Air Merah Village, South Labuhan Batu Regency. The type of research used is descriptive research with a qualitative approach. This study took as many as six people as resource persons. The data collection technique used in this research is interviews. The results of this study indicate that the Implementation of Participatory-Based Planning in the Construction of a Suspension Bridge in Air Merah Village, Labuhan Batu Selatan Regency has not been fully implemented properly. Because the actions taken have not gone as expected, where the government does not carry out deliberation to make decisions for the construction of the suspension bridge. Therefore, the construction of this suspension bridge was not built as expected by the local community. In planning the suspension bridge construction, the community has not been fully involved, because in the socialization only the landowners are invited to participate. This causes problems in the community because the suspension bridge construction point is not in accordance with what the community needs and expects. Thus, the government is expected to be able to defend the rights of the people as much as possible in planning a development. The policy regarding the construction of suspension bridges has several points that are not implemented properly. The government is expected to carry out intensive socialization with the community to provide an understanding of each policy by prioritizing a win-win solution, meaning that every policy made by the government does not override the rights of the community.